Video shooter : storytelling with HD cameras - Braverman, Barry (Routledge, 2014)
"Tired of the all the Digital Filmmaking guidebooks that give you only the nuts and bolts of how to use a camera? Video Shooter 2e takes that how-to knowledge and takes it a step further by showing you how to craft a story in your video. Barry Braverman is a highly experienced shooter whose name is gold in the field. This book covers everything from framing a shot, to lighting, to the type of camera (and tripod) one should use, and perhaps most importantly--how to translate the use of all this equipment and techniques into a story. Humorous and opinionated, the author provides anecdotes and full-color illustrations that help you to learn the tricks of the trade. He gets right to the point of what you need to know to get good shots--and on a budget. New to this edition: * more up-to-date techniques involving HD technology* more coverage on the multi-skillset required of today's filmmmakers (who are asked to act simulataneously as Director, Director of Photography, Cinematographer, Sound Recordists, etc.)*Website including craft tips, equipment review/blogs, and a teacher's corner to support use of the book in film studies/digital media class (includes student work completed in class using the text)"--Provided by publisher